Performance Evaluation: A Comparative Study Between Indian and Foreign Equity Mutual Funds - Rama Devi, V.; Kumar, Nooney Lenin (Indian Journal of Finance, 2010)
Saving for the future is good. Investing for it is even better. Mutual funds have many benefits that make them one of the most efficient, cost-effective, and easy investments available. They are also ideal vehicles for individual investors who don’t have the time, willingness or ability to manage their own portfolio of bonds or stocks. Indian mutual fund industry is one of the fastest growing sectors in the Indian capital and financial markets. The mutual fund industry in India has seen dramatic improvements in quantity as well as quality of product and service offerings in recent years.